The Role of Pasraman Kilat in Raising Sradha and Bhakti of Teenagers - Nerawati, Ni Gusti Ayu Agung; Sudarsana, I Ketut (Jayapangus Press, 2020)
Pasraman kilat is a social institution in the community to provide non-formal Hindu religious learning. Pasraman kilat aims to improve the knowledge of Hindu religion from a formal school. This study used a qualitative method and data collection used observation, interviews, and literature studies. Based on the results, the role of pasraman kilat was very useful. It can be seen not only from the series of activities but also from the results. Teenagers who followed the pasraman kilat, apply and practice the learning outcomes in everyday life, both in religious activities and in daily activities. This suggests that learning is effective and acceptable to teenagers.